Utilizing Item Response Theory Approach for Calibrating Items in the Final Assessment of Islamic Cultural History Subject - Prihatin, Rani Putri; Fatonah, Siti; Ahmad, Iqbal Faza (Jurnal Pendidikan Agama Islam, 2022)
Purpose –The aim of this exploratory descriptive study with a IRT approach is to evaluate the quality of items used in the final assessment of 10th grade Islamic cultural history subject at Madrasah Aliyah Negeri (MAN) 2 Bantul Yogyakarta. Design/methods/approach–Data was collected through documentation of student responses at the end of the year assessment. Student response data were analyzed using the item response theory approach. Findings – Based on the analysis of 25 questions on the Islamic Cultural History subject at MAN 2 Bantul, the study concludes that the instrument fits the 1 PL model (Logistics parameter), as indicated by the results of the model fit test. The parameter analysis of item difficulty level with the 1 PL model reveals that 7 items fall under the very easy category, 5 items under the easy category, 9 items under the medium category, and 4 items under the very difficult category. Notably, none of the items fall under the difficult category in this 1 PL model. Research implications/limitations –The findings on the distribution of item difficulty levels could guide educators in revising and improving the quality of assessment tools, ensuring that the questions are well-balanced and challenging enough to effectively evaluate students' knowledge and skills. Moreover, the absence of items falling under the difficult category in the 1 PL model suggests a need for more rigorous and challenging items to enhance the validity and reliability of the assessment instrument. Originality/value–The research value of this study lies in its contribution to the development of a valid and reliable assessment tool in the field of Islamic cultural history subject.